Clinical characteristics and short-term recovery of hyposmia in hospitalized non-severe COVID-19 patients with Omicron variant in Shanghai, China - Shen, Jun; Wu, Li; Wang, Ping; Shen, Xiaolei; Jiang, Yuhan; Liu, Jianren; Chen, Wei (Frontiers in Medicine, 2022)
Background: Olfactory dysfunction is a common neurological symptom of Corona Virus Disease 2019(COVID-19). Little is known about hyposmia after COVID-19 infection with Omicron variant in Chinese population. Objective: To investigate the incidence, clinical characteristics and recovery of hyposmia in hospitalized non-severe COVID-19 patients with Omicron variant in Shanghai, China. Methods: Three hundred and forty-nine Chinese non-severe COVID-19 patients with Omicron variant were enrolled in designated hospital to investigate the incidence of hyposmia in hospitalization and the recovery rate one month later. We compared the demographic, clinical features and treatment outcomes, as well as laboratory parameters between patients with and without hyposmia. Results: The cross-sectional survey showed that 22(6.3%) hospitalized patients with non-severe COVID-19 had hyposmia. Patients with hyposmia were younger (61.5 vs. 72.0, p=0.002), had more related clinical symptoms (sore throat, cough, poor appetite, diarrhea, myalgia and taste impairment, etc), more proportions of moderate clinical type (31.8 vs. 13.5%, p=0.028) and longer hospitalized duration (11 vs. 8 days, p=0.027) than those without hyposmia. Whereas, there were no significant differences regarding gender, comorbidity and nucleic acid conversion time between the two groups. Laboratory subgroup analyses demonstrated that patients with hyposmia had slightly low serum IL-6 and TNF-α levels. However, both of the levels were not associated with hyposmia occurrence in multivariate regression analyses. Further follow-up study disclosed that 16 of 22 (72.7%) hyposmia patients had recovered olfaction one month later. Serum IL-6 and TNF-α levels were consistent between hyposmia recovered and persistent patients. Conclusions: Although the incidence of hyposmia after Omicron variant infection is relatively low and the short-term recovery rate is quite high, patients with hyposmia are prone to have more proportions of both upper and lower respiratory tract involvements, gastrointestinal and neurological symptoms, contributing to longer hospitalized duration.